Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-342
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Multistage Navier-Stokes Solver: Part I — Multistage Modeling Using Bodyforces and Deterministic Stresses

Abstract: A novel multistage compressor performance analysis method based on the three-dimensional Reynolds averaged Navier-Stokes equations is presented in this paper. This approach is a “continuous interface plane approach” where deterministic stresses are used to ensure continuous physical properties across interface planes. The average unsteady effects due to neighboring blades and/or vanes are approximated using deterministic stresses along with the application of bodyforces. Bodyforces are used to account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 0 publications
0
39
2
Order By: Relevance
“…neglecting the purely temporal part of the deterministic stresses and retaining only the spatial part [3]. Some approaches based on this assumption compute explicitly the terms required for the closure and neglect the viscous terms [15], [6]. Bardoux [6] has presented some results obtained on the same CME2 compressor that is studied here.…”
Section: Hierarchy Of the Additional Termsmentioning
confidence: 99%
“…neglecting the purely temporal part of the deterministic stresses and retaining only the spatial part [3]. Some approaches based on this assumption compute explicitly the terms required for the closure and neglect the viscous terms [15], [6]. Bardoux [6] has presented some results obtained on the same CME2 compressor that is studied here.…”
Section: Hierarchy Of the Additional Termsmentioning
confidence: 99%
“…To accelerate the convergence, local time stepping [23], implicit residual smoothing [24] and multigrid [25] are employed. The mixing plane method [18] is employed in the steady simulation and the continuous interface plane method [3] is used in the time-averaging simulation for the interblade row coupling. The domain scaling method is employed in the unsteady simulation [26].…”
Section: Solutionsmentioning
confidence: 99%
“…Adamczyk et al [2] proposed the first model using overlapping grids for all blade rows without interface planes. Rhie et al [3] demonstrated a continuous interface plane approach using overlapping grids for downstream row only. LeJambre et al [4] employed this type of analysis in a multistage axial compressor design study and effectively improved a baseline design using results from the averagepassage-based flow simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responding to this limitation, several researchers have worked on the Mixing-plane method [1][2][3][4][5][6][7] to approximate the unsteady flow field that occurs in multistage turbomachines with a steady flow. The idea is that by adding a mixing layer between adjacent blade rows, the flow can essentially "mix" and thus smooth out the unsteady variations that would occur in a real multistage machine.…”
Section: Introductionmentioning
confidence: 99%